Emergence of oncofetal plasticity is ubiquitous in early colorectal cancers - Julian R. Buissant des Amorie; Joris H. Hageman; Sascha R. Brunner; Suzanne E. M. van der Horst; Maria C. Puschhof; Arne van Hoeck; Inge van Lierop; Sjors Middelkamp; Lisa van der Schee; Sven van Kempen; Folkert Morsink; Robin Geene; et al. (Nature, 2026)
Abstract Metastasis formation is classically considered a late-stage event in colorectal cancer evolution. Yet the time and spatial patterning by which metastatic competence is acquired remain poorly understood 1,2 . Here we show that metastasis-associated oncofetal cell states already emerge at the earliest stages of colorectal cancer, concurrent with invasive front formation. However, although necessary for metastasis, we detect them ubiquitously among early non-metastatic cancers, highlighting extra bottlenecks such as immune evasion. To understand how oncofetal cells first emerge, we generated multiregional organoid models that reflect successive tumour progression stages within individual early-stage colorectal cancers. Whole-genome sequencing and growth factor-dependency assays exclude tumour cell-intrinsic acquired traits. By contrast, single-cell spatial atlases of the tumour microenvironment before and after malignant transformation revealed stereotypic patterning of fibroblast subtypes resembling normal tissue architecture, resulting in distinct regional microenvironments. At the onset of malignant growth into the submucosa, the first cancer-associated fibroblasts to appear strongly resemble submucosal trophocytes and colocalize with oncofetal cell states at invasive fronts. Functionally, fibroblast–organoid cocultures confirm that these trophocyte-like cancer-associated fibroblasts induce plastic transitioning to oncofetal states. Thus, interactions between tumour and submucosal fibroblasts directly following malignant transformation dictate the timing and location at which oncofetal plasticity first occurs during colorectal cancer progression.